2014
DOI: 10.1002/2013sw001024
|View full text |Cite
|
Sign up to set email alerts
|

MAG4 versus alternative techniques for forecasting active region flare productivity

Abstract: MAG4 is a technique of forecasting an active region's rate of production of major flares in the coming few days from a free magnetic energy proxy. We present a statistical method of measuring the difference in performance between MAG4 and comparable alternative techniques that forecast an active region's major-flare productivity from alternative observed aspects of the active region. We demonstrate the method by measuring the difference in performance between the “Present MAG4” technique and each of three alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 35 publications
2
45
0
Order By: Relevance
“…However, since the underlying mechanisms leading to the generation of solar eruptions have not yet been indisputably determined, no sufficient conditions of solar eruptivity have yet been established. Solar flare predictions are thus still strongly driven by empirical methods (e.g., Yu et al 2010;Falconer et al 2011Falconer et al , 2014Barnes et al 2016). Nowadays most predictions rely on the determination and characterization of solar active regions through the use of several parameters and the statistical comparison with the historical eruptivity of past active regions presenting similar values of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, since the underlying mechanisms leading to the generation of solar eruptions have not yet been indisputably determined, no sufficient conditions of solar eruptivity have yet been established. Solar flare predictions are thus still strongly driven by empirical methods (e.g., Yu et al 2010;Falconer et al 2011Falconer et al , 2014Barnes et al 2016). Nowadays most predictions rely on the determination and characterization of solar active regions through the use of several parameters and the statistical comparison with the historical eruptivity of past active regions presenting similar values of these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…A complex photosphere causes a complex corona, a complex corona stores energy, and this stored energy is released as solar flares ). There have been many searches for a connection between coronal activity (flares) and the photospheric magnetic field (Ahmed et al 2013;Falconer et al 2011;Mason & Hoeksema 2010;Yuan et al 2010;Huang et al 2010;Jing et al 2010Jing et al , 2006Yu et al 2010a,b;Welsch et al 2009;Ireland et al 2008;Conlon et al 2008;Georgoulis & Rust 2007;Leka & Barnes 2007;Schrijver 2007;Wang 2006;Barnes & Leka 2006;Guo et al 2006;McAteer et al 2005a;Abramenko 2005;Meunier 2004;Abramenko et al 2003;Leka & Barnes 2003b;Hagyard et al 1999;Zhang et al 1994). Despite such research, a fully consistent and causal relationship has not yet been found (e.g., see conclusions in Mason & Hoeksema 2010;Leka & Barnes 2007;and Hagyard et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Despite such research, a fully consistent and causal relationship has not yet been found (e.g., see conclusions in Mason & Hoeksema 2010;Leka & Barnes 2007;and Hagyard et al 1999). Nevertheless, there is optimism that photospheric measures may yield some insight into imminent eruptive behavior (e.g., Falconer et al 2011;Yu et al 2010a;Schrijver 2007;Guo et al 2006;Jing et al 2006;Abramenko 2005;Leka & Barnes 2003b).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations